2018
DOI: 10.5539/jel.v7n6p67
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Project-Based Learning on Achievement and Student Views: The Case of AutoCAD Programming Course

Abstract: The aim of the study was to determine the impact of project-based learning on academic achievements of vocational school of higher education students and to investigate their views on the topic. In the study, a mixed descriptive design where qualitative and quantitative data were both collected and analyzed. The quantitative part was conducted with relational screening method and the qualitative part was conducted with descriptive analysis method. The study group included 13 freshmen students attending the voc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
2
10
1
1
Order By: Relevance
“…The next contribution of this research pertains to the impacts of PjBL on the improvement of students' academic self-efficacy. While previous studies have demonstrated the benefits of PjBL in improving student academic performance (Cȩlik et al, 2018;Huysken, et al, 2019), conceptual understanding (Coruhly & Nas, 2018), and research skills (Saliba et al, 2017), this study revealed its effects on participants' self-efficacy -a critical contributor to academic success. This finding of the current study can assist first-year academic coordinators and faculty to more efficiently utilize PjBL in their course redesign efforts, especially for accomplishing the learning outcomes that students' have historically struggled with.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…The next contribution of this research pertains to the impacts of PjBL on the improvement of students' academic self-efficacy. While previous studies have demonstrated the benefits of PjBL in improving student academic performance (Cȩlik et al, 2018;Huysken, et al, 2019), conceptual understanding (Coruhly & Nas, 2018), and research skills (Saliba et al, 2017), this study revealed its effects on participants' self-efficacy -a critical contributor to academic success. This finding of the current study can assist first-year academic coordinators and faculty to more efficiently utilize PjBL in their course redesign efforts, especially for accomplishing the learning outcomes that students' have historically struggled with.…”
Section: Discussioncontrasting
confidence: 60%
“…Thus, the findings of this study can help us better understand the positive effects of prior course redesign efforts (Hearne & Henkin, 2011;Vaughan, 2010;Wilson et al, 2018) by associating them with improvements in students' self-efficacy (Fini et al, 2018). It can also be argued that the evidence presented in this study supports the claim that students' perceptions of their increased academic abilities are not unwarranted and can be affirmed by their academic performance in the future (Cȩlik et al, 2018;Das et al, 2019;Huysken et al, 2019;Olson, 2017). This knowledge can serve as an important implication for all FYS faculty and staff working with students who are struggling academically, enroll in colleges under-prepared, or find it particularly hard to overcome academic barriers and roadblocks.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Similarly, Chen and Yang's (2019) meta-analysis of the effects of the PjBL method on academic achievement compared to traditional methods revealed that the method had an average to higher positive effect on academic achievement. According to findings of similar studies, project-based learning contributes to higher levels of perception and learning by creating an effective classroom environment and ensures high student achievement and performance (Belwal et al, 2020;Cifci, 2015;Çelik et al, 2018;Hugerat, 2016). Participants in another study stated that to the research findings PjBL method increases active participation, makes the lesson comprehensible, efficient, instructive, motivating, and makes learning permanent (Şahin et al, 2020).…”
Section: Statementsmentioning
confidence: 99%
“…In this context, the PBL is used in many different disciplines. Among these disciplines, there are disciplines such as science (Tierney et al, 2020), Science, Technology, Engineering and Mathematic (STEM) (Tseng et al, 2013), nursery (Wu et al, 2018), foreign language (Sadeghi, Biniaz & Soleimani, 2016), information technologies (Celik et al, 2018).…”
Section: Journal Of Computer and Education Researchmentioning
confidence: 99%